Let $G\rightarrow X$. Show that $stab(g\cdot x)$ is conjugate to $stab(x)$.

To make $G$ act on itself by conjugation, take $X = G$ and let $ g \times x = gxg^{-1}$ Here $g \in G$ and $x \in G$ Since $e \times x = exe^{-1} = x$ and \begin{align*} g_1 \circ (g_2 \circ x) & = g_1 \circ (g_2xg_2^{-1}) \\ & = g_1(g_2xg_2^{-1})g_1^{-1} \\ & = (g_1g_2)x(g_1g_2)^{-1} \\ & = (g_1g_2) \circ x \\ \end{align*} Conjugation is a group action.

Did I do this correctly?

  • 3
    $\begingroup$ No, you just showed part of the proof that conjugation is a group action. Showing that the stabilizers are conjugate is not the same as showing that conjugation is a group action. $\endgroup$ – Qudit Apr 5 '15 at 2:38
  • $\begingroup$ see my new attempt, and tell me how that is $\endgroup$ – All About Groups Apr 6 '15 at 22:54

$G$ acts on $X$ : We have a relation between stabilizers : $$ z\in G_x \Leftrightarrow z\cdot x=x \Rightarrow (gzg^{-1} )\cdot (g\cdot x ) =g\cdot x \Rightarrow gG_xg^{-1}\subset G_{g\cdot x} $$

So $$ (G_x\subset )\ g^{-1} G_{g\cdot x} g \subseteq G_x $$ so that $$ G_x =g^{-1} G_{g\cdot x } g $$


First, consider some $z\in stab(x)$. Thus, $z\cdot x = x$, which implies that $(gzg^{-1})\cdot(g\cdot x) = gz(g^{-1}\cdot g)\cdot x) = g(z\cdot x) = g\cdot x$ and therefore $gzg^{-1}\in stab(g\cdot x)$ and $stab(g\cdot x)$ is conjugate to $stab(x)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.